Pengaruh Metode Pembelajaran Inquiry Berbasis Visualisasi Materi Larutan Elektrolit dan Nonelektrolit di Kelas X IPA SMA Negeri 1 Kawangkoan - Reynaldi Assa; Wilson Alexander Rombang; Hardin Foster Rares (Chemistry Department, Universitas Negeri Manado, 2019)
The purpose of this study is to examine the effect of visualization-based inquiry learning methods on student learning outcomes in electrolyte and non-electrolyte solution material. This research was conducted in Kawangkoan 1 Public High School, in the even semester X IPA students, 2018/2019 academic year. Class X IPA students 1 (n = 31) as the experimental class and class X IPA 2 (n = 32) as the control class. The test used in this study statistical t test with significance level α = 0.05 with the testing criteriat> ttable then H0 is rejected and H1 accepted. The results obtained in this test obtained tcount 5.25> ttable 1.670. This test is done not to improve student learning outcomes beyond the minimum standard of completeness criteria in school but this testing is only to see the effect of visualization based inquiry learning methods on student learning outcomes. Based on the results obtained it can be concluded that there are differences in student learning outcomes applied with conventional learning models (control class) and visualization based inquiry learning methods (experimental class)